28: Cost-Effectiveness Analysis Comparing Pre-Diagnosis Treatment for Autism Spectrum Disorder with the Ontario Autism Program. Issue 6 (1st June 2014) - Penner, M; Rayar, M; Bashir, N; Roberts, W; Hancock-Howard, R; Coyte, P
Abstract: BACKGROUND: Autism Spectrum Disorder (ASD) is associated with significant lifetime costs. The Early Start Denver Model (ESDM) has shown efficacy in children with ASD as young as 18 months. New service delivery models propose providing ASD-targeted treatment to young children who show signs of ASD before a diagnosis. There are no studies examining the cost-effectiveness of this model. OBJECTIVES: We performed a cost-effectiveness analysis comparing the costs and dependency-free life years (DFLYs) generated by pre-diagnosis intensive ESDM (ESDM-I), pre-diagnosis parent-delivered ESDM (ESDM-PD) and the Ontario Status Quo (SQ). DESIGN/METHODS: We took a government perspective and a time horizon to age 65. We constructed a decision-analytic model delineating three treatment pathways. We assumed 37% of children received Early Intensive Behavioural Intervention (EIBI). The ESDM-I and ESDM-PD contributed gains of 17.6 and 4.94 IQ points, respectively. These were added to expected mean IQs for children who enter EIBI before and after age four, and those who do not receive EIBI. IQ outcomes were stratified into >70 and <70. Each IQ stratum was assigned a probability of achieving an Independent (60 DFLYs), Semi-Dependent (30 DFLYs) or Dependent (0 DFLYs) outcome. Costs for each pathway were determined using the budget of an ESDM pilot project and government publications. An incremental cost-effectiveness ratio (ICER) was calculated. Discount rates of 0%, 3% and 5% were applied and a probabilistic sensitivity analysis was conducted to account for variability in costs and effects. RESULTS: With no discount rate applied, the SQ program cost an average of $380, 000 per child over the lifetime and generated an average of 4.23 DFLYs. The ESDM-PD had an average cost of $386, 000 and generated 6.86 DFLYs. The ESDM-I cost $410, 000 for 7.36 DFLYs. The ICER for ESDM-PD compared to SQ was $2400 per DFLY gained, and the ICER for ESDM-I compared to SQ was $9, 500 per DFLY gained. The ICER for the ESDM-I compared to the ESDM-PD was $47, 500 per DFLY gained. The pattern of increasing costs and increasing effectiveness remained for both the ESDM-PD and ESDM-I when 3% and 5% discount rates were applied. CONCLUSIONS: From a government payer perspective, parent-delivered, pre-diagnosis ASD interventions may offer an efficient model for service delivery. Our model did not produce the savings seen in previous economic evaluations due to use of poorer prognostic expectations in our analysis. More prognostic evidence is needed for adults with ASD, particularly those who have received EIBI.